Identifying new isatin derivatives with GSK-3 inhibition capacity through molecular docking and bioassays - Britto, Karolinni B. (2020)
The semi-synthesis of 11 isatin derivatives was achieved through bimolecular nucleophilic substitution and click chemistry. Seven new compounds were obtained. All chemical structures were determined by infrared spectroscopy (IR), nuclear magnetic resonance spectrometry (NMR) and high-resolution mass spectrometry (HRMS) data. These derivatives were evaluated for their anti-GSK-3 activity and all isatin derivatives (N-alkyl and 1,2,3-triazolic) exhibited strong inhibitory activity, with 2b and 4h exhibiting remarkable potency. In addition, docking studies were performed with 2b and 2e models to unravel the molecular mechanism underlying the polar interactions on the GSK-3 ATP-binding site.